PROGRAM KEMITRAAN MASYARAKAT REMAJA DALAM UPAYA PENCEGAHAN PENYEBARAN PENYAKIT COVID 19 MELALUI PHBS DI KELURAHAN MOJOLANGU KEC.LOWOKWARU MALANG - Fiashriel Lundy; Pudji Suryani; Rahmadyo Yudhi (Politeknik Kesehatan Kemenkes malang, 2022)
This Covid 19 disease does not only attack the elderly but also teenagers, especially if they have an unfavorable lifestyle. This disease also causes high mortality. For this reason, promotive and preventive efforts are needed. The role of youth/youth who are expected to be able to bring forward their village and create a healthy and prosperous youth community life through Youth Organization activities through youth health cadres is the right step. Each element in the community plays a maximum role in accordance with its position. The cooperation of Karang Taruna youth and the community will have a major impact on healthy community life. The activities carried out were in the form of training which was carried out for 3 days to determine the knowledge of teenagers in preventing the transmission of covid 19 with PHBS through the Implementation of the V_D_J Health Protocol and Immunity Improvement. The results of the implementation of the activities were evaluated using a questionnaire that was measured pre-post, with an average pre-test score of 10% in the poor knowledge category, while the post-test results obtained 90% in the good knowledge category, with an increase in knowledge about Prevention of the Spread of Covid 19 with PHBS (Application of the VDJ Health Protocol and Immunity Enhancement).Training for Youth in Mojolangu Lowokwaru Village, Malang City is effectively carried out, in addition to increasing knowledge about preventing the transmission of Covid 19 with PHBS, teenagers in Mojolangu Lowokwaru Village, Malang City are expected to be able to further educate peers, families and communities in their area through Youth Health Cadres. formed.